2013
DOI: 10.15275/rusomj.2013.0307
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cardiovascular risk factors among university students in Turkey: a cross-sectional survey

Abstract: Background -Recent data indicate increasing rates of mortality from cardiovascular (CV) disease in Turkey. This study aimed to evaluate CV disease risk factors among university students in Northern Turkey. Methods -In this cross sectional descriptive study, 302 students were randomly recruited (171 females (57%) and 131 males (43%), mean age of 20±2.1 years). Blood glucose, cholesterol profile (total, high density lipoprotein (HDL) and low density lipoprotein (LDL) cholesterols), triglyceride, glycosylated hae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
1
5
0
1
Order By: Relevance
“…The study found among university students from 22 low and middle income and emerging economy countries a prevalence of overweight or obese that compares with previous studies in transitional societies [5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30]. In agreement with a number of studies mainly from Asia [14,15,22], it was found that male gender was associated with overweight/obesity in those populations.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…The study found among university students from 22 low and middle income and emerging economy countries a prevalence of overweight or obese that compares with previous studies in transitional societies [5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30]. In agreement with a number of studies mainly from Asia [14,15,22], it was found that male gender was associated with overweight/obesity in those populations.…”
Section: Resultssupporting
confidence: 67%
“…Studies among university students in developing countries show high prevalence of overweight and obesity: Africa (Nigeria: 10% [ 5 ]; Egypt: 25.3%–59.4% [ 6 , 7 ], South Africa: 10.8%–24% [ 8 , 9 ]; Asia (Bangladesh: 20.8% [ 10 ]; China: 2.9%–14.3% [ 11 , 12 ]; Malaysia: 20%–30.1% [ 13 , 14 ], Thailand: 31% [ 15 ], Pakistan: 13%–52.6% [ 16 , 17 ], and India: 11%–37.5% [ 18 , 19 , 20 , 21 ]; Latin America (Colombia: 12.4%–16.7% [ 22 ]; Mexico: 31.6% [ 23 ], the Middle and Near East (Saudi females: 47.9% [ 24 ], Oman: 28.2% [ 25 ] Kuwait: 42% [ 26 , 27 ], Iran 12.4% [ 28 ], and Turkey: 10%–47.4% [ 29 , 30 ]). Although there are prior studies on obesity/overweight in students in individual developing countries, this study collected data from 22 countries (low, lower middle, upper middle and high income countries) in different regions (Africa, Asia, The Caribbean and South America) using the same methodology, which allows for direct comparison across countries.…”
Section: Introductionmentioning
confidence: 99%
“…Por lo que se deben aportar datos consistentes sobre los factores de riesgo cardiovascular (FRCV) en los jóvenes, evitando sus consecuencias, y además debe ser un primer destino de los esfuerzos de prevención para reducir las enfermedades cardiovasculares (13)(14)(15)(16).…”
unclassified
“…Prevalence of CVRF is quite variable across different social categories of Russian people [32-34, and present study]. The situation is similar in other countries [1,2]. Results of Russian studies on the prevalence of CVRF [32][33][34] are difficult to compare the cardiovascular health status assessment.…”
Section: Discussionmentioning
confidence: 73%
“…High prevalence of cardiovascular risk factors (CVRF) is a great problem of primary prevention in many countries [1,2]. Main CVRF are as follows: age, gender, smoking, unhealthy diet, sedentary lifestyle, stress, increased body weight and obesity, elevated blood pressure (BP), hyperglycaemia and hypercholesterolaemia [3].…”
Section: Introductionmentioning
confidence: 99%